Development of Electronic Storybooks to Improve the Environmental Care Character of Elementary Schoool Students in Pancasila and Citizenship Education Subjects - Sunaryati, Titin; Sudharshono, Muhammad; Edy, Sarwo (Proceeding International Pelita Bangsa, 2023)
This study aims to develop teaching material products in the form of electronic story books to increase the character of caring for the environment in the Android-based Pancasila and Citizenship Education subjects. The type of research used is Research and Development (R&D). This study uses data collection techniques in the form of questionnaires and observations. The data collection instruments used were product rating scales, character self-assessment questionnaires about caring for the environment, character observation guidelines and teacher and student interviews. Research data were analyzed using the percentage formula. Based on the assessment of media experts, the electronic storybook product scored 80.1% in the good category, according to linguists, the electronic storybook product scored 84.95% in the good category, and the material expert's assessment was 86.35% in the good category. The use of electronic story books for students in elementary schools on individual scale tests obtained an average percentage of 87.25% with very good criteria, 88.70% small-scale trials with very good criteria then carried out large-scale product trials on average percentage of 86.20% while the results of data analysis of operational trial results show significant results of electronic story books in the formation of environmental care, planting environmental care, and maintaining environmental care. Electronic storybooks on class III Pancasila and citizenship education lessons at Cijengkol 02 State Elementary School, Bekasi Regency, West Java Province, are appropriate for use as additional learning media in enhancing the environmental care character of students in elementary schools.